Prognostic significance of pretreatment thrombocytosis in endometrial cancer: an Israeli Gynecologic Oncology Group study. Issue 11 (26th November 2021) - Tal, Ori; Eitan, Ram; Gemer, Ofer; Helpman, Limor; Vaknin, Zvi; Leytes, Sofia; Lavie, Ofer; Ben-Arie, Alon; Amit, Amnon; Namazov, Ahmet; Ben Shahar, Inbar; Atlas, Ilan; et al.
Abstract : Objective: Endometrial cancer prognosis is related to stage, histology, myometrial invasion, and lymphovascular space invasion. Several studies have examined the association between pretreatment thrombocytosis and patient outcomes with contrasting results regarding prognosis. Our aim was to evaluate the association of pretreatment platelet count with outcomes in endometrial cancer patients. Methods: This is an Israeli Gynecologic Oncology Group multicenter retrospective cohort study of consecutive patients with endometrial cancer, who underwent surgery between January 2002 and December 2014. Patients were grouped as low risk (endometrioid G1-G2 and villoglandular) and high risk (endometrioid G3, uterine serous papillary carcinoma, clear cell carcinoma, and carcinosarcoma). Those with stage I disease were compared with stages II–IV. Disease stages were reviewed and updated to reflect International Federation of Gynecology and Obstetrics (FIGO) 2009 staging. All patients underwent pelvic washings for cytology and total abdominal or laparoscopic hysterectomy with bilateral salpingo-oophorectomy. Pelvic lymph node assessment was performed in patients with tumors of moderate–high risk histology or deep myometrial invasion. Para-aortic sampling was performed at the surgeon's discretion. Patients were categorized by pretreatment platelet count into two groups: ≤400×10 9 /L and >400×10 9 /L (defined as thrombocytosis). Clinical and pathological features were compared using Student t-test, χ 2 or Fisher's exact test. Survival measures were plotted with the Kaplan-Meier method and compared using the log-rank test. A Cox proportional hazards model was used for multivariable comparison of associations. Results: Of the 1482 patients included, most had stage I disease (961; 74.8%) and most had endometrioid histology (927; 64.1%). A total of 1392 patients (94%) had pretreatment platelet counts ≤400×10 9 /L and 90 (6%) had pretreatment thrombocytosis. Patients with thrombocytosis had a significantly higher rate of high-grade malignancy, advanced stage, lymphovascular space invasion, low uterine segment involvement, and lymph node metastases. They also had shorter 5 year disease-free survival (65% vs 80%, p=0.003), disease-specific survival (63% vs 83%, p<0.05) and overall survival (59% vs 77%, p<0.05). On multivariate analysis, an elevated pretreatment thrombocyte count remained a significant independent predictor for disease-specific survival and overall survival. Conclusions: Pretreatment thrombocytosis is an independent prognostic factor for decreased disease-specific survival and overall survival among patients with endometrial cancer, and can serve as a predictor of poor outcome.